Profile of Students’ 21st Century Skills in Digital Learning Using The Contextual Teaching and Learning (CTL) Model - Atika Ulya Akmal; Yohandri; Abdul Razak (Universitas Pendidikan Ganesha, 2023)
The 21st century skills are skills that really need to be developed to face the current digitalization era. Looking at the current conditions, students' 21st century skills are not very prominent and are not well developed so that students need new innovations that can support 4C skills. The purpose of this study was to analyze the 21st century skill profile of first semester Elementary School Teacher Study Program students in the elementary physics basic concepts course. This type of research is descriptive research. The sample of this research was 110 students selected with a specific purpose or by purposive sampling technique. The data collection techniques used are questionnaires, interviews, and observation. The data were analyzed using descriptive statistics which would show the percentage of the number of students per category. The results of this study indicate that for creative thinking skills, collaboration and communication the percentage of students is in the near standard category. As for creative thinking skills, the percentage of students is in the substandard category. This shows that students' 21st century skills still need to be improved. learning activities that facilitate the emergence of 21st century skills need to be carried out continuously or continuously so that students are accustomed to and achieve the desired standards. The conclusion of this study is that students' 21st century skill profiles in digital learning with CTL are in a status close to a good standard, except for creative thinking skills that still require some extra treatment to improve them.